Effect of world lacrosse sixes match play on neuromuscular performance in international men`s lacrosse players - Ripley, N.; Fahey, J.; Collier, M.; Comfort, P. (International Journal of Strength and Conditioning, 2025)
Sixes lacrosse is a new sport to be included in the 2028 Olympics, however there is limited understanding on the demands of Sixes lacrosse competition. Purpose: To observe the effect of Sixes lacrosse on acute fatigue. Methods: Eleven international male Sixes lacrosse players (24.82 ± 2.58 years, 180.17 ± 8.84 cm, 90.14 ± 7.63 kg) participated within the present study, playing in five competitive matches over three-days. Three countermovement jump (CMJ) trials were performed pre- and post-match. Results: Very large (d = 1.35 [0.51-2.17]) decreases in system weight (SW), a moderate increase in jump height (JH) (d = 0.67 [-0.02-1.31]) and a moderate decrease in average relative braking force (ARBf) (d = 0.68 [-0.03-1.27]) were observed from pre-post one match. A moderate (d = 0.76 [0.07-1.42]) decrease in SW, with a small increase in average relative propulsive force (ARPf) (d = 0.30 [-0.31-0.90]) were observed from pre-post three matches. Very large increases in JH (d = 1.69 [0.73-2.61]) and time to take off (d = 1.43 [-0.40-2.45]) with a large increase in countermovement displacement (d = 1.05 [0.29-1.78]) and a large decrease in ARBf (d = 0.84 [0.13-1.52]), with no meaningful changes were observed for SW (d = 0.03 [-0.56-0.62]), or ARPf (d = 0.04 [-0.56-0.63]) observed from pre-post international tournament. Conclusion: The results of this study have implications on recovery within Sixes lacrosse players during international tournaments. Moreover, the high levels of observed fatigue would likely require a period of restitution following international tournament.